Effects of climate and topography on the diversity anomaly of plants disjunctly distributed in eastern Asia and eastern North America. Issue 10 (2nd August 2021) - Yin, Xue; Qian, Hong; Sui, Xinghua; Zhang, Minhua; Mao, Lingfeng; Svenning, Jens‐Christian; Ricklefs, Robert E.; He, Fangliang
Abstract: Aim: Differences in physiography have been proposed to explain the diversity anomaly for vascular plants between environmentally similar regions of eastern Asia (EAS) and eastern North America (ENA). Here, we use plant species within disjunct genera to examine whether differences in topography contribute to the diversity anomaly and whether the richness–environment relationships differ between regions. Disjunct plants are used to ensure that the diversity anomaly relates to post‐disjunction evolution and diversification rather than regional differences in clade ages or immigration. Location: EAS and ENA. Time period: Current. Major taxa studied: Plant taxa disjunctly distributed in EAS and ENA. Methods: We compiled county‐level plant distribution data, and calculated species richness and variables of topography and climate within unit grid cells. We compared estimated coefficients of region effects among models, where richness was fitted with or without topography and climate. Topography and climate were also used to separately model within‐region spatial diversity patterns using spatial simultaneous autoregressive error models. Results: The coefficients of region effects varied from −.776 for the model only including region to −.309 when topography was controlled for, but remained significant. Climate dominated the spatial diversity patterns in ENA. In contrast, the influence of climate (14.2%) on species richness was weaker than that of topography (18.3%) in the warm area of EAS. Relations to elevation and temperature varied between regions, shifting between positive and negative relationships in several cases. Main conclusions: Our results demonstrate that variability in local topography contributes to the strong regional anomaly in plant species richness between EAS and ENA. Nevertheless, the diversity anomaly persists after controlling for local topography and climate. EAS and ENA also exhibit contrasting richness–environment relationships, providing another divergent aspect between the EAS–ENA disjunct floras. Our findings highlight that regional differences in topography or other environmental factors may underlie the diversity anomaly.